Maximizing productivity of linseed (Linum usitatissimum L.) through nitrogen and sulphur application: MAXIMIZING PRODUCTIVITY OF LINSEED THROUGH NITROGEN AND SULPHUR APPLICATION - K M SHASHANK; JAIDEV SHARMA; PRADEEP RAJPUT; PRADEEP KUMAR KANAUJIYA; SHRAVAN KUMAR MAURYA (Journal of Oilseeds Research, 2026)
Due to the deficiency of nitrogen (N) and sulphur (S) in the semi-arid conditions of the Gwalior region, improving the productivity of linseed (Linum usitatissimum L.) remains a substantial challenge. The deficiency and imbalanced use of these nutrients in the region result in reduced linseed yields. Therefore, a field experiment was conducted during the rabi season of 2024-25 on the sandy loam soil at the Crop Research Centre, ITM University, Gwalior (M.P.), to evaluate the effect of different levels of N and S on the growth and yield of linseed. The results revealed that the application of N at 100 kg/ha exhibited superior performance across a range of parameters, including growth characteristics, yield attributes, seed yield (2001 kg/ha), and stover yield (3015 kg/ha). Furthermore, the highest growth and yield attributes, along with seed yield (2046 kg/ha) and stover yield (3011 kg/ha), were recorded with the application of 60 kg S/ha. The findings of this study suggest that the application of N and S is a sustainable and effective strategy for enhancing the productivity, profitability, and quality of linseed in the semi-arid regions of Madhya Pradesh.